A distinct double-ring LH1–LH2 photocomplex from an extremophilic phototroph - Kazutoshi Tani; Kenji V. P. Nagashima; Risa Kojima; Masaharu Kondo; Ryo Kanno; Issei Satoh; Mai Kawakami; Naho Hiwatashi; Kazuna Nakata; Sakiko Nagashima; Kazuhito Inoue; Yugo Isawa; et al. (Nature Communications)
Abstract Halorhodospira (Hlr.) halophila strain BN9622 is an extremely halophilic and alkaliphilic phototrophic purple sulfur bacterium isolated from a hypersaline lake in the Libyan Desert whose total salinity exceeded 35% at pH 10.7. Here we present a cryo-EM structure of the native LH1–LH2 co-complex from strain BN9622 at 2.22 Å resolution. Surprisingly, the LH1–LH2 co-complex consists of a double-ring cylindrical structure with the larger LH1 ring encircling a smaller LH2 ring. The Hlr. halophila LH1 contains 18 αβ-subunits and additional bacteriochlorophyll a (BChl a) molecules that absorb maximally at 797 nm. The LH2 ring is composed of 9 αβ-subunits, and the BChl a molecules in the co-complex form extensive intra- and inter-complex networks to allow near 100% efficiency of energy transfer to its surrounding LH1. The additional LH1-B797 BChls a are located in such a manner that they facilitate exciton transfer from monomeric BChls in LH2 to the dimeric BChls in LH1. The structural features of the strain BN9622 LH1–LH2 co-complex may have evolved to allow a minimal LH2 complex to maximize excitation transfer to the core complex and effectively harvest light in the physiologically demanding ecological niche of this purple bacterium.